A Simple and Highly Sensitive Turn-on Schiff Base Type Naked-eye Fluorescent Sensor for Aluminum Ion in Living Cells - Sedat Keskin (Acta Chimica Slovenica, 2019)
Six different Schiff bases to be used as turn-on fluorescent probes based on photoinduced electron transfer (PET) mechanism for the recognition of aluminum ions were successfully synthesized and characterized. The binding abilities of synthesized compounds with different metal cations was investigated by absorption and emission spectra. From the spectrophotometric experiments, it was seen that compound SK-1 displayed an excellent fluorescence response towards targeted aluminum ions probably due to its suitable chelating structure. Furthermore, such compound SK-1 also showed high sensitivity and selectivity response towards aluminum ions over other competing ions. In addition, the potential biological applications of SK-1 to detect aluminum ions in living cells were also investigated and results showed that fluorescence sensor SK-1 could be a promising probe for determining and/or monitoring aluminum ions in both biological and/or chemical samples.